TEACHING PRIMARY CLASS STUDENTS TO SOLVE TIME PROBLEMS - Bozorov, Murot Nashvandovich (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
Teaching time to elementary school students is important because this knowledge is useful for them in terms of time management. This research aims to describe the process of teaching time to students in elementary schools in Uzbekistan. This is a case study research (descriptive study case) where the researcher explains the Focus on providing a detailed and accurate description of the case, including the background, context, and outcomes. The data collection method used was observation. The researcher made observations during classroom learning when the teacher explained time material to students in elementary schools in Uzbekistan. The results of the research showed that the teacher succeeded in explaining the time material by providing lots of story problem practice. The conclusion obtained from this research is that story questions are an effective medium for teaching time material to students in elementary schools in Uzbekistan.